2017
DOI: 10.1088/1361-6420/aa8414
|View full text |Cite
|
Sign up to set email alerts
|

An explicit reconstruction method for magnetic resonance electrical property tomography based on the generalized Cauchy formula

Abstract: This paper presents an explicit reconstruction formula for magnetic resonance electrical property tomography (MREPT). We derive a Dbar problem from the time-harmonic Maxwell equations under the assumptions that , , and , where the z-axis is parallel to the body axis, is the measured magnetic field, and . Then, by using the generalized Cauchy formula, the electrical conductivity and permittivity are explicitly expressed in terms of their boundary values and the measured magnetic field. We also propose an itera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…The Dirichlet-type integral formula reconstructs EPs correctly outside of the region where |∂H + | and |E z | are low when the true boundary condition is given. As mentioned in Section 2.1, this spot-like artifact occurs in regions where |∂H + | and |E z | become zero and most state-of-the-art methods using single channel birdcage coils have the same problem [19], [20], [29], [31], [32]. The method of displacing this spot-like artifact by inserting a dielectric pad was proposed in [29] and is applicable to both our previous and proposed methods.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The Dirichlet-type integral formula reconstructs EPs correctly outside of the region where |∂H + | and |E z | are low when the true boundary condition is given. As mentioned in Section 2.1, this spot-like artifact occurs in regions where |∂H + | and |E z | become zero and most state-of-the-art methods using single channel birdcage coils have the same problem [19], [20], [29], [31], [32]. The method of displacing this spot-like artifact by inserting a dielectric pad was proposed in [29] and is applicable to both our previous and proposed methods.…”
Section: Resultsmentioning
confidence: 97%
“…This is due to the assumption that ∂ z H + 0. In [32], we have already proposed an iterative method to correct the error in this assumption. We confirmed that a single iteration significantly suppressed the error in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ammari et al, the forward problem of MREPT is also modeled as a PDE and an inverse problem approach is used to iteratively find the EPs by minimizing the norm of the difference between the measured and calculated B1+. More recently, in Fushimi and Nara and Nara et al, a 2‐stage algorithm is developed whereby the axial electric field is also estimated together with the EPs.…”
Section: Introductionmentioning
confidence: 99%